Abdulla Avloniy asarlarining ilmiy pedagogik tavsifi - Zayniddinova Sevinch Jaloliddin qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, the life and work of Alloma Abdulla Avloni, an enlightened scientist, one of the mature representatives of Jadid literature, who left an indelible mark in Uzbek literature with his incomparable works and lyrics, as well as his works, their ideological meaning and ideas put forward talked about. In addition, some information about scientific pedagogic views and attention and recognition of education in the works of Abdulla Avloni is also presented.